Wide-range, high-accuracy multiple microwave frequency measurement by frequency-to-phase-slope mapping. (March 2020) - Wang, Di; Du, Cong; Yang, Yuchen; Zhou, Weinan; Meng, Tong; Dong, Wei; Zhang, Xindong
Highlights: The Brillouin gain-loss compensation way is used to extend the measurement range. Applying the method of monotonous frequency-to-phase-slope mapping based on SBS. The frequency measurement range is validity extended from 2 V B to 4 V B . Extremely high measured frequency accuracy of 4 MHz is theoretically realized. Abstract: A photonics-based method of instantaneous frequency measurement (IFM) based on Stimulated Brillouin scattering (SBS) is proposed and theoretically analyzed. The principle of the technique is the employment of the Brillouin gain-loss compensation and monotonous frequency-to-phase-slope mapping (FTPSM) method, where the FTPSM is realized utilizing the correlation between Brillouin phase shift and unknown signal frequency. With the new technique, the frequency of a signal and multiple unknown RF signal can be measured and due to bypass a fundamental trade-off between measurement range and accuracy through our method, resulting in the measurement range of the system is extended from 2 V B to 4 V B with a higher accuracy ~4 MHz. In addition, the influences of the pump light wavelength variation and power change on the performance of the IFM system are discussed.